Disciplined Subjectivity In Historical Evidence: Balancing Objectivity And Interpretation - Zhilwan Tahir (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
The article reviews how historians can balance objectivity with subjectivity in their assessment of historical evidence, which is arguably the major theme in both historiography and in the philosophy of history: How does one write history with epistemic integrity while recognizing and accepting that the discipline is interpretively mediated? The article engages the theoretical work of Leopold von Ranke, E. H. Carr, Hayden White, Frank Ankersmit, and Michael Novick, while also placing their debates within broader philosophical and historiographical frameworks. The outcome of this discussion positions that objectivity and subjectivity are not mutually exclusive; that is, a disciplined acknowledgment of subjectivity, via reflexively engaging with sources, narrative decisions, and interpretative frameworks, enhances methodological rigor and provides a transparent history to the past. Thus, while the discussion is theoretical, examples of the reflexive subjectivity in action span from Ranke's work in the archives and diplomatic accounts to studies of Holocaust testimony and colonial memory. The study advances a model of disciplined subjectivity as a methodological bridge between objectivity and interpretation, enabling historians to produce coherent, transparent, and ethically responsible narratives